The internet industry, other information technologies and sustainable development - Gentzoglanis, Anastassios (CIENCIA ergo-sum; Vol. 3 Núm. 2 (1996): CIENCIA ergo-sum (julio-octubre 1996), 2017)
We are currently in the midst of the formation of a new industry within the broader information technology (IT) sectors, the Internet industry. This industry is presently composed of a relatively small number of firms and a vast array of users who make worldwide transactions instantaneously escaping even from the most fundamental laws and/or regulations of the countries where transactions take place. The ever increasing demand for an array of commercial, educational and entertainment services and Mosaic's user-friendly interface has made the Internet an integral part of our social and economic activities with important ramifications for the broader information technologies sector. Internet's pervasiveness creates great opportunities as well as challenges to both developed and developing countries. It is expected that ITs would have an adverse effect on the wages of low-skilled workers in industrialized countries and a positive effect on the wages of high-skilled workers. This is so because competition from low-wage countries combined with wage rigidities in the labour markets in industrialized countries creates more unemployment in the low-skilled jobs in industrialized countries. Inequalities therefore become even worse with the introduction and the widespread application of ITs. The pattern of inequality becomes even worse in developing countries where the levels of education among groups of citizens are more unequal.